Effects of dietary oils with different fatty acid profiles on rumen fermentation, microbial population and nutrient digestibility in goats - Ibrahim, Nur Atikah (2015)
Study have been conducted to investigate the effects of oils with different fatty acid profiles on rumen fermentation, microbial population and nutrient digestibility in goats. Sixteen male goats fitted with rumen cannula were randomly assigned to four experimental dietary treatments. The first group acted as control (CNT) and was given basal diet; whereas the second, third and fourth groups were supplemented with 6% of olive oil (OL), palm olein oil (PO) and sunflower oil (SF) respectively. The feed was analysed for proximate analysis. The rumen content was collected for enumeration of protozoa, analysis of fibre degrading bacteria and methanogens using qPCR, and chemical analysis for ammonia and VFA. For the second experiment, sixteen male goats were used for digestibility experiment. Approximately, 10% of total faecal collection was sampled for chemical analysis of nutrient and their digestibility was calculated. The GLM procedure from SAS was used to analyse the parameters. The mean pH of the rumen fluid pH values were significantly affected by day of sampling (P < 0.01). Higher mean of ammonia concentrations was observed in CNT (42.6 mg/L) compared to others and was significantly affected by diet (P < 0.01), day of sampling (P < 0.05) and diet × day of sampling interaction (P < 0.05). The mean of total VFA concentration (mmol) was higher in SF and OL groups and significantly affected by diet treatments (P < 0.05). Molar proportion of acetate, propionate and isobutyrate were affected by diet (P < 0.05) and day of sampling (P < 0.05). Molar proportion of butyrate and valerate were affected by day of sampling (P < 0.05). The mean number of protozoa was lower (P < 0.05) in treatment groups compared to CNT. There were significant differences in apparent digestibility of CP (P < 0.05) and EE (P < 0.01) of treatment groups compared to CNT. Real-time PCR have been used to quantify three cellulolytic bacteria species which are, F. succinogens, R. albus and R. flavefaciens, together with protozoa, methanogen archeae and total bacteria for day 0, day 18 and day 30 with significant observed on R. albus (P < 0.05) and protozoa population (P <0.01). As a conclusion, supplementation of dietary oils improved rumen fermentation as total VFA production increased whereas ammonia and protozoa counts decreased significantly. Therefore, the results suggest that vegetables oil reduced and maintain low level of rumen protozoa population during supplementation in goats and help savings on protein supplements, reduce the excretion of nitrogen and its negative environmental impact.